Driving Digital Transformation in Lima’s SMEs: Unveiling the Role of Digital Competencies and Organizational Culture in Business Success - Lorena Espina-Romero; Raquel Chafloque-Céspedes; Jorge Izaguirre Olmedo; Rossmery Albarran Taype; Angélica Ochoa-Díaz (Administrative Sciences)
This study examines the impact of digital competencies (DCs) and organizational culture (OC) on digital transformation (DT) in small and medium-sized enterprises (SMEs) in metropolitan Lima. Using a non-experimental and cross-sectional design, 307 business owners were surveyed using a previously validated questionnaire. Data were analyzed through partial least squares structural equation modeling (SEM-PLS). The results show that DCs have a direct and significant impact on DT, being the main driver of this process. Additionally, OC acts as a partial mediator between DCs and DT, although its influence is lesser, compared with DCs. The study highlights the importance of DCs in driving digitalization in SMEs, while OC facilitates, although does not solely determine, the success of the digital transformation process. Despite the limitations and the cross-sectional nature of the study, the findings provide valuable insights for SMEs in emerging economies and offer a basis for future research on the factors influencing digital transformation in similar contexts.